The Remittance Market in India : Opportunities, Challenges, and Policy Options - Afram, Gabi G. (World Bank, 2012)
In chapter one, this report maps the patterns and characteristics of migration flows from India; in chapter two, it provides a detailed discussion of remittance flows to India in terms of their importance, sources, uses, trends, costs, and links to financial access. In chapter three, the report describes the remittance market (the players, the regulatory framework, as well as the existing operational schemes), setting the stage for chapter four, which presents a diagnostic of the remittance market based on the General Principles for International Remittance Services (GPs). The diagnostic covers the legal and regulatory framework, payment system infrastructure, market transparency and level of consumer protection, market structure, level of competition among remittance service providers, as well as market governance. It analyzes the existing situation in India and provides detailed recommendations (including lessons learned from international best practices) that are aimed at increasing competition in the remittance industry, providing broader access to payment system infrastructure, enhancing transparency, and ensuring a sound and predictable legal and regulatory framework. Several of the actions could set a basis for leveraging remittances to achieve other important public policy goals such as broadening financial access, expanding financial inclusion, and both strengthening and deepening the financial sector. The report was prepared through (a) background research (data research and mining, literature review, collection of relevant material and information, and background research), (b) a field visit in 2009 (a team of experts visited India and conducted interviews and focus groups with all relevant stakeholders and major institutions active in the remittance market), and (c) surveys of both the authorities and the market players.